COMPARATIVE CHARACTERISTICS OF NATIVE CULTURE AND IMMOBILIZED CULTURE ON MODIFIED PECTIN FOR YOGHURT AT DIFFERENT TIME AND STORAGE CONDITIONS - Vovkohon, A. H. (Scientific Progress & Innovations, 2019)
The presence of living microorganisms in the cultures for cultured milk drinks including yoghurt requires their regulated storage conditions. Native lactic acid bacteria have relatively short storage time. The storage time and the resistance of yoghurt culture microorganisms to inhibiting factors can be increased by cells immobilization. Thus, the research objective was to study the influence of storage conditions and time on the activity of the culture immobilized on modified pectin and native culture for yoghurt. The experimental cul-ture samples were stored in refrigerator at the temperature of 3−4 ˚С and at room temperature (18−22˚С) for 42 months. Every 6 months the culture samples were taken and put into standardized milk. The fermentation was done during 8 hours by thermostat method. Sensor analysis was made and the titrated acidity of the final product of fermentation with native and immobilized cultures for yoghurt was defined. The appearance, consistency and flavor of yoghurt obtained by means of native and immobilized cultures stored at 3−4 ˚С and used after 6−24 months were the same. The final products had a distinct cultured milk taste without any foreign flavor, moderately viscous formed milk clot. The selected samples of native culture from refrigerator stored for 30 months were not good for obtaining yoghurt of high quality. The final prod-uct had a viscous consistency with the taste of acid milk. Using the culture immobilized on modified pectin taken from refrigerator after 30−42 months of storage enabled to receive high quality yoghurt according to sensor indices. The activity of native culture stored at room temperature was stable during 18 months and the activity of immobilized culture made 36 months. It was experimentally proved that titrated yoghurt acidi-ty produced with native culture stored for 24 months in refrigerator and 18 months at the temperature 18−22 ˚С corresponded to the standard requirements and made within 89.5−93.2 ˚Т. The similar acidity of cultured milk products was established while using immobilized yoghurt culture samples taken after 42 months of storage in refrigerator and after 36 months of storing at room temperature. Thus, the immobiliza-tion of yoghurt culture microorganisms on modified pectin favors the prolongation of their storage time (shelf life) both at room temperature and in refrigerator.